2009
DOI: 10.1017/s0033291709005303
|View full text |Cite
|
Sign up to set email alerts
|

Specific cognitive deficits in a group at genetic high risk of schizophrenia

Abstract: Spatial memory capacity and planning processing speed may represent cognitive endophenotypes characterising the genetic predisposition to schizophrenia in this HR group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
2
16
0
2
Order By: Relevance
“…Reaction time, an indicator of speed of processing, is increased in relatives of patients (Birkett et al, 2007). Young relatives at risk for SZ have reduced processing speed even after controlling for IQ as shown by the Edinburgh High-Risk Study (EHRS) ( p  = 0.044) (Byrne et al, 2003; Cunningham Owens and Johnstone, 2006; O'Connor et al, 2009), as well as our studies which will be described later. These deficits might be state-independent given that psychotic symptoms do not alter the severity of speed of processing deficits in patients (O'Connor et al, 2009).…”
Section: Nature Of Neurocognitive Deficits In Young Relatives At Risksupporting
confidence: 65%
See 2 more Smart Citations
“…Reaction time, an indicator of speed of processing, is increased in relatives of patients (Birkett et al, 2007). Young relatives at risk for SZ have reduced processing speed even after controlling for IQ as shown by the Edinburgh High-Risk Study (EHRS) ( p  = 0.044) (Byrne et al, 2003; Cunningham Owens and Johnstone, 2006; O'Connor et al, 2009), as well as our studies which will be described later. These deficits might be state-independent given that psychotic symptoms do not alter the severity of speed of processing deficits in patients (O'Connor et al, 2009).…”
Section: Nature Of Neurocognitive Deficits In Young Relatives At Risksupporting
confidence: 65%
“…WM in all subsystems is impaired in first episode patients (Zanello et al, 2009) and unaffected first degree relatives (Conklin et al, 2005; Saperstein et al, 2006; Horan et al, 2008). Relatives of SZ patients perform poorly on spatial WM (Awh et al, 1998; Saperstein et al, 2006) and spatial memory capacity (O'Connor et al, 2009). Several studies report impairments in verbal, spatial and object WM domains with a graded pattern of impairment; deficits in patients > relatives > controls are observed for verbal WM (Niendam et al, 2003; Conklin et al, 2005).…”
Section: Nature Of Neurocognitive Deficits In Young Relatives At Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we recruited controls selected at random from the general population; such controls are likely to be more representative of the population than in previous studies but this approach may lead to less sensitivity to detect between-group differences. The Edinburgh high-risk study, which was not drawn from a clinic sample, found that symptomatic expression did not affect cognitive performance (O'Connor et al, 2009). However, this study did show that Spatial Working Memory and Stockings of Cambridge differentiated the family risk group from controls.…”
Section: Discussionmentioning
confidence: 99%
“…85 Other studies have also suggested that patients with schizophrenia may have a reduced memory span across modalities. 86,87 Two meta-analyses that examined working memory in patients with schizophrenia have suggested that the latter showed a substantial effect size for working memory deficits, regardless of modality, although there may be more consistent impairments in visual working memory. 88,89 However, it also has been suggested that working memory deficits may be the result of a general encoding deficit, particularly stimulus encoding (i.e., the transformation and preparation of presenting stimuli into a format facilitating collateral functions, including those of "working memory").…”
Section: Working Memory Deficitsmentioning
confidence: 99%